Evaluation of efficacy and safety of coenzyme Q10 in pediatric hemodialysis patients: a randomized controlled trial - Salma A. Rahman Sharaf; Sarah Farid Fahmy; Heba M. Adel Abou Zaghla; Ahmed Hussein Hassan; Sara Mahmoud Zaki (Future Journal of Pharmaceutical Sciences)
Abstract Background There is evidence from clinical trials that coenzyme Q10 significantly improves mitochondrial function and decreases oxidative stress and cardiovascular disease in adult hemodialysis patients. However, we have never fully investigated its role in pediatric patients before. This study aimed to assess the effects of coenzyme Q10 supplementation on oxidative stress and inflammatory markers in pediatric hemodialysis patients. This was a prospective, randomized, double-blinded, placebo-controlled trial. Thirty-six pediatric hemodialysis patients were recruited and simply randomized to receive either oral coenzyme Q10 (3–5 mg/kg) daily or placebo daily for 12 weeks. Results Using the Mann–Whitney test, children in the intervention group showed a significant reduction in the median percent change of blood urea nitrogen from baseline of − 58.18 versus − 9.6 in the placebo group (p = 0.002). The median percent change of serum malondialdehyde significantly decreased by − 55.68 in the intervention group, while it increased by 39.75 in the placebo group (p < 0.001). Additionally, the median percent change from baseline in serum tumor necrosis factor-α levels significantly decreased by − 46.69 in the intervention group and increased by 8.5 in the placebo group (p = 0.03). Conclusion Supplementation of oral coenzyme Q10 may have beneficial effects on oxidative stress and inflammatory markers in pediatric hemodialysis patients. This study emphasized the potential efficacy of an average coenzyme Q10 dose of 4 mg/kg/day in pediatric hemodialysis patients; this gives the green light for other researchers to confidently evaluate larger doses as an attempt to control the systemic inflammation in this patient population. Further research is needed to determine whether coenzyme Q10 treatment improves clinical outcomes such as infection, hospitalization, cardiovascular events, and mortality in pediatric hemodialysis patients. Trial Registration Clinical trials.gov, NCT05170893, Registered 28 December 2021, https://clinicaltrials.gov/study/NCT05170893?cond=NCT05170893&rank=1 . Graphical abstract